Creative City and the Sustainable Life: A Study on the Making of Cultural Spaces in Osaka and Bandung - Sawangchot, Viriya (Journal of Urban Culture Research, 2016)
The terms creative city and creative class are notable in how urban development is understood today, and stress the importance of culture, art, and creativity in the urban context. This research critically examines the notion of creative city as a causal mechanism in changes in production and consumption in the urban and suburban regeneration of Osaka, Japan, and Bandung, Indonesia. It also draws attention to the effects of the “creative city model” in the cultural policies of these two cities within globally competitive economic platforms. By doing so, the research critiques this model vis-à-vis the potential of artists, academics, art activists, and creative people to seek alternative cultural sustainability.